2014
DOI: 10.1016/j.amepre.2014.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Smoking Among U.S. Hispanic/Latino Adults

Abstract: Background Prior national surveys capture smoking behaviors of the aggregate US Hispanic/Latino population, possibly obscuring subgroup variation. Purpose To describe cigarette use among Hispanic/Latino adults across subgroups of age, sex, national background, socioeconomic status, birthplace and degree of acculturation to the dominant US culture. Methods Cross-sectional survey of 16,322 participants in the Hispanic Community Health Study/Study of Latinos aged 18 to 74 years old, recruited in Bronx NY, Chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
117
2
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 200 publications
(128 citation statements)
references
References 16 publications
6
117
2
3
Order By: Relevance
“…Although the Hispanic population typically consumes plant sources of calcium, from which calcium is absorbed less effectively than dairy sources, our study found no differences in dietary calcium intake from dairy foods between groups, which may be a result of acculturation. 19,28,38,39 However, malabsorption of dairy products consumed by Hispanic women may contribute to lower bioavailability of actual calcium and vitamin D. 19 As the best practice to maintain adequate nutrition is through diet and Hispanic women may not regularly choose dairy foods or be able to properly absorb dairy products, Hispanic women should be educated about culturally relevant foods rich in nutrients to promote bone health.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although the Hispanic population typically consumes plant sources of calcium, from which calcium is absorbed less effectively than dairy sources, our study found no differences in dietary calcium intake from dairy foods between groups, which may be a result of acculturation. 19,28,38,39 However, malabsorption of dairy products consumed by Hispanic women may contribute to lower bioavailability of actual calcium and vitamin D. 19 As the best practice to maintain adequate nutrition is through diet and Hispanic women may not regularly choose dairy foods or be able to properly absorb dairy products, Hispanic women should be educated about culturally relevant foods rich in nutrients to promote bone health.…”
Section: Discussionmentioning
confidence: 99%
“…However, level of acculturation was not recorded with a validated acculturation scale and may impact dietary and lifestyle behaviors, as less acculturated Hispanic women may be less likely to engage in behaviors to promote bone health. 28,38,39 Lifestyle behaviors to promote bone health throughout the life cycle are necessary to prevent bone loss and osteoporosis. Clinical applications of this study include informing all women about the importance of bone health maintenance throughout life with proper lifestyle behaviors, especially adequate consumption of calcium and vitamin D and increased physical activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interviewer‐administered questionnaires were used to collect information on age, sex, annual household income, education level, Hispanic/Latino background, employment status, and health insurance. Lifetime history of cigarette smoking and other smoking‐related variables were assessed by self‐reported questionnaires 23. Alcohol consumption was obtained through a self‐reported questionnaire on lifetime and current use of alcoholic beverages, the frequency of use per week, and type of alcohol consumed, adapted for use in Hispanic/Latino adults 24.…”
Section: Methodsmentioning
confidence: 99%
“…The remainder are of other Central American, South American, or other Hispanic or Latino origin. 13 Previous research has found that smoking prevalence and level (ie, light vs heavy smoking) among subgroups of Latinos varies significantly, eg, Mexicans tend to have higher smoking prevalence than Dominicans 14 and lower prevalence compared with…”
Section: Introductionmentioning
confidence: 99%